Sosialisasi Dampak Konversi Lahan terhadap Perubahan Iklim di Nagari Sungai Durian Padang Pariaman - Ulni, Arie Zella Putra; Afrital Rezki; Erna Juita; Dasrizal; Elvi Zuriyani (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
The initial survey in Nagari Sungai Durian found that there are many forms of land use. Each of these land uses is closely related to one another. This shows that there are good practices in land management. The purpose of this community service activity is to increase the knowledge and abilities of partners in knowing the impact of land conversion. Increasing public knowledge on global climate change disasters. This service activity is carried out by delivering material to the public about the impact of land conversion on climate change. The results of community service activities are as follows: 1). The community already knows the impact of converting their agricultural land. The impact is felt not only on them alone but globally. 2). The impact of conversion of agricultural land is generally very large in the social and economic fields. The result of this socialization is that the community is ready to protect their agricultural land to reduce climate change.